Measuring the level of self-awareness among faculty members in universities: demographic factors - AL-Tkhayneh, Khawlah M.; Hadi, Samer Abdel; Ellala, Ziyad Kamel (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to measure the level of self-awareness among university faculty members, considering various demographic variables such as gender, academic specializations, and experience. The research was conducted on a sample of faculty members from four universities in Jordan and the United Arab Emirates (UAE): two from Jordan and two from the UAE. A sample of 172 faculty members was selected using an appropriate non-probability sampling technique. The researchers invited the entire study sample to participate in the self-awareness scale (SAS), developed using a translated Arabic version. The study found that the level of self-awareness among the sample was moderately average, with a mean score of 3.54. Additionally, according to the survey, there were no discernible gender disparities in self-awareness among university faculty members. However, there were statistically significant differences among faculty members in the sub-dimensions of realistic caution and self-reflection based on the experience variable, favoring faculty members with 11 or more years of experience. Significant differences were also observed in realistic awareness and indifference to external cues among faculty members specializing in humanities and social sciences compared to those in other specializations.